Review: The status of the endangered Eld’s deer (Rucervus eldii) and conservation actions in Thailand - Ronglarp Sukmasuang; Naris Bhumpakphan; William J McShea; Worawidh Wajjwalku; Boripat Siriaroonrat; Sumate Kamolnoranart; Marnoch Yindee; Tarasak Nipanan; Banpot Maleehuan; Krittaphas Khanthathongsakuldee; Chattraphas Pongcharoen; Nantida Sutummawong; Warisara Thomas (Society for Indonesian Biodiversity, 2022)
Abstract. Sukmasuang R, Bhumpakphan N, McShea WJ, Wajjwalku W, Siriaroonrat B, Kamolnoranart S, Yindee M, Nipanan T, Maleehuan B, Khanthathongsakuldee K, Pongcharoen C, Sutummawong N, Thomas W. 2022. Review: The status of the endangered Eld’s deer (Rucervus eldii) and conservation actions in Thailand. Biodiversitas 23: 5020-5034. The endangered Eld’s deer (Rucervus eldii) once roamed throughout the plains and dry forests of South and Southeast Asia. However, due to heavy poaching and habitat loss, the population has declined drastically and has disappeared from many of its historical ranges. They are presently found in some natural areas of India, Myanmar, Cambodia, Lao PDR, and Hainan Island, China. Thailand used to be the distribution center of the species, where two subspecies, the R.e. thamin and R.e. siamensis, were found. However, both subspecies have disappeared from the natural resources of Thailand since the early 1990s. Many conservation programs have been conducted to save this species in Thailand, such as captive breeding and reintroduction. Our literature review revealed that currently, more than a thousand R.e. thamin are housed in over 20 wildlife breeding facilities and 109 R.e. siamensis in 8 breeding facilities. Based on the workshops on conservation and restoration of the species, suitable genetic selection can create populations suitable for return to protected forest areas in Thailand. At present, more than 554 R.e. thamin have been released back into the wild in 8 wildlife sanctuaries, 3 national parks and 1 non-hunting area and 27 R.e. siamensis were released in 2 wildlife sanctuaries in Thailand. The follow-up of the deer in the release areas was flawed. Major knowledge gaps include recent trends in the population dynamics, habitat selection, diet items and threats. Identifying and restoring suitable dry forest habitats for reintroduction are also keys for species conservation.